Deixis in English Textbook Used for Business Management Students: A Pragmatic Analysis - Safi'i, Muhamad; Arnoi, Khoirun Nisaa' (English Education : English Journal for Teaching and Learning, 2025)
The study aims to measure how well the textbook supports students in attaining pragmatic proficiency in context-dependent professional communication. Applying a descriptive qualitative research, the study analyzes samples of text in the textbook according to the five deixis categories: person, place, time, discourse, and social deixis. The findings reveal that textbooks include diverse deictic expressions, but their pragmatic nature and context are not necessarily emphasized. Person deixis features prominently, as they are frequently used in business communication. However, other categories are still underrepresented, possibly limiting students from engaging with complex, hierarchical, and implicit relationships. These findings highlight the need for more pragmatically enriched material within ESP materials in order to better equip studentss for professional communication tasks.